2014
DOI: 10.1586/17474086.2014.903794
|View full text |Cite
|
Sign up to set email alerts
|

RARAfusion genes in acute promyelocytic leukemia: a review

Abstract: The t(15;17)(q24;q21), generating a PML-RARA fusion gene, is the hallmark of acute promyelocytic leukemia (APL). At present, eight other genes fusing with RARA have been identified. The resulting fusion proteins retain domains of the RARA protein allowing binding to retinoic acid response elements (RARE) and dimerization with the retinoid X receptor protein (RXRA). They participate in protein-protein interactions, associating with RXRA to form hetero-oligomeric complexes that can bind to RARE. They have a domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
80
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 127 publications
0
80
0
2
Order By: Relevance
“…To date, 11 variant fusion genes in APL, all involving the RARα gene, have been reported in a small percentage of APL cases. The partner genes include zinc finger and BTB domain-containing 16 ( ZBTB16 ; 11q23), nucleophosmin ( NPM ; 5q35), nuclear mitotic apparatus ( NuMA ; 11q13), signal transducer and activator of transcription (STAT) 5β ( STAT5b ; 17q21), protein kinase A (PKA) regulatory subunit type ( PRKAR1A ; 17q24), FIP1-like 1 ( FIP1L1 ; 4q12), BCL6 corepressor ( BCoR ; Xp11), oligonucleotide/oligosaccharide-binding fold-containing 2A ( OBFC2A ; 2q32) [6], transducin β-like 1 X-linked receptor 1 ( TBLR1 ; 3q26) [7], general transcription factor II-I ( GTF2I ; 7q11.23) [8], and interferon regulatory factor 2 binding protein 2 ( IRF2BP2 ; 1q42.3) [9]. The X-RARα (X:partner product) fusion pattern highlights the central role of RARα in the pathogenesis of APL.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 11 variant fusion genes in APL, all involving the RARα gene, have been reported in a small percentage of APL cases. The partner genes include zinc finger and BTB domain-containing 16 ( ZBTB16 ; 11q23), nucleophosmin ( NPM ; 5q35), nuclear mitotic apparatus ( NuMA ; 11q13), signal transducer and activator of transcription (STAT) 5β ( STAT5b ; 17q21), protein kinase A (PKA) regulatory subunit type ( PRKAR1A ; 17q24), FIP1-like 1 ( FIP1L1 ; 4q12), BCL6 corepressor ( BCoR ; Xp11), oligonucleotide/oligosaccharide-binding fold-containing 2A ( OBFC2A ; 2q32) [6], transducin β-like 1 X-linked receptor 1 ( TBLR1 ; 3q26) [7], general transcription factor II-I ( GTF2I ; 7q11.23) [8], and interferon regulatory factor 2 binding protein 2 ( IRF2BP2 ; 1q42.3) [9]. The X-RARα (X:partner product) fusion pattern highlights the central role of RARα in the pathogenesis of APL.…”
Section: Introductionmentioning
confidence: 99%
“…A unique chromosome translocation t(15; 17)(q22; q21) found in the majority of APL patients leads to the formation of the promyelocytic leukemia retinoic acid receptor α (PML-RARα) fusion gene (1). The fusion protein encoded by the PML-RARα gene polymerizes and combines with retinoid-X receptor.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion protein encoded by the PML-RARα gene polymerizes and combines with retinoid-X receptor. The resultant protein complexes enhance histone deacetylase, thus repressing the transcription of the gene and disrupting the retinoic acid signal pathway under physiological concentrations of retinoic acid (1). This change results in the excessive growth of malignant promyelocytes and an inhibition of granulocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…PML-RARA fusion most often arises via the classic t(15; 17)(q24.1;q21.2) translocation, which results in fusion of the 5 ′ end of PML (exons 1-3) to the 3 ′ end of RARA (exons 3-9) [De Braekeleer et al, 2014]. This fusion typically resides on the derivative chromosome 15 resulting in a chimeric oncoprotein, which is considered the primary "driver" mutation.…”
mentioning
confidence: 99%
“…Among the insertions reviewed by Grimwade et al [2000], the cryptic PML-RARA fusion was typically found in the derivative chromosome 15q (75% cases) and much less frequently in the derivative 17q. Alternatively, RARA can be found fused to another gene (approximately 1-2%), most frequently ZBTB16 due to the recurrent translocation t(11; 17)(q23;q21), but other rare variant partner genes have also been reported [De Braekeleer et al, 2014]. Among all these variant forms, RARA is consistently involved supporting its role in APL pathogenesis, which has been implicated in regulation of development, differentiation, apoptosis, and granulopoiesis.…”
mentioning
confidence: 99%